The impacts of culture on corporate governance: Corporate governance’s effectiveness - Gonçalves, Marta Barros (2023)
This study analyzes the different impacts that the cultural dimensions created and developed by Hofstede have on corporate governance and the effect of the management of a company when influenced by a specific cultural background. The empirical study is based on a literature review conducted through articles and studies in the areas of economic and cultural impact, as well as the scores obtained from the EIKON database, and the scores studied by Hofstede. The combination of these values is then correlated using the statistical system SPSS to determine if there is a significant impact on a company's economic performance and management. The results obtained are consistent with predictions made in various previous studies, which demonstrate that certain dimensions will always have more impact than ones that are not as related to economic and financial areas. These results are consistent with earlier predictions and are coherent with the research carried out in the initial chapters, which support the hypotheses presented in this dissertation. Furthermore, the research suggests that certain cultural dimensions will always have a more significant impact on company management, as the correlation between the scores of cultural dimensions and governmental scores will be more significant, whether positively or negatively.